Tinjauan Masa Depan Keberlanjutan Program Konservasi Primata dan Kopi di Jawa Tengah, Indonesia - Annisa, Choiriatun Nur; Farahdita, Wanda Laras (Forestry Faculty of Hasanuddin University, 2023)
Kayupuring village has a dense forest which also the habitat for Javan Gibbon. Coffee plants is also present in the forest and utilised by the local community for their livelihood. Therefore, forest protection and utilisation activities need to be aligned to ensure sustainability. Swara Owa is one of the stakeholders conducting that approach through a program of Coffee and Primates Conservation Project. This study aims to overview the future sustainability of the program. System thinking is employed, and data were obtained through desk study and literature review with the scope of 2013-2019. Four main variables selected to describe the system are forest degradation (ecosystem), coffee price (wellbeing), local institutional strength – Village Forest Community Institution/LMDH (social), and forest conservation awareness (cultural paradigm). The interaction of the program system can be explained that the higher the conservation awareness level, the higher the forest quality, then the stronger LMDH, the higher coffee price; and the higher coffee price makes conservation awareness high. The higher coffee price, the people are more aware to conservation issue because the coffee comes from an area of the wildlife habitat. The three main strategies to achieve ideal vision are tenure mapping, policy intervention, and community participation and empowerment.